2008
DOI: 10.1002/smj.704
|View full text |Cite
|
Sign up to set email alerts
|

What do they know? The effects of outside director acquisition experience on firm acquisition performance

Abstract: This article contributes to the literature on board effectiveness by being perhaps the first to systematically examine how the nature of outside directors' prior experience, and resulting expertise, will influence the performance of a focal firm's strategic initiatives. Our theoretical model is grounded in the psychological literature on expertise and its role in group decision making effectiveness. We focus on outside director expertise in acquisition decision making, and its implications for the performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
260
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 309 publications
(276 citation statements)
references
References 99 publications
4
260
1
5
Order By: Relevance
“…For each sample firm, we then sum the cases for all outside directors on the board to obtain a final number representing its board's international investment experience. We exclude inside directors in the calculation to focus on a board's unique contribution outside of what the firm's executives can provide [3,8,15]. The following is the formula of director FDI experience:…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For each sample firm, we then sum the cases for all outside directors on the board to obtain a final number representing its board's international investment experience. We exclude inside directors in the calculation to focus on a board's unique contribution outside of what the firm's executives can provide [3,8,15]. The following is the formula of director FDI experience:…”
Section: Methodsmentioning
confidence: 99%
“…According to expertise literature, individuals develop expertise on complex decision makings as they accumulate substantial amounts of relevant experience in that particular field [8,26]. In contrast to general decision makings of which information can be clearly processed and critical message can be articulately identified, complex decisions are usually subject to information overload, vague cause-and-effect relation, and ambiguity of unforeseen contingencies.…”
Section: Specific Learning From Director Fdi Experience Within Focal mentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, high levels of executive directorships are associated with high access to information that leads to high quality decision-making (Zahra and Stanton, 1988;Weir et al, 2002;Nicholson and Kiel, 2003), with positive consequences firm valuation. Further, it has been argued that corporate boards dominated by INEDs tend to stifle managerial initiative and strategic actions (Pfeffer, 1973;Baysinger and Butler, 1985;McDonald et al, 2008), which arise from excessive managerial supervision (Baysinger and Hoskisson, 1990;Haniffa and Hudaib, 2006), and thereby leading to lower market valuation.…”
Section: Ineds and Firm Valuation: Theory Evidence And Hypothesis Dementioning
confidence: 99%
“…However, and whereas there is a theoretical agreement that INEDs perform crucial roles in improving corporate monitoring and valuation (Fama, 1980;Jensen, 1993;McDonald et al, 2008), the empirical evidence on the effect of the presence of INEDs on firm valuation is mixed. A number of reasons, however, have been suggested that may account for the conflicting results of prior studies.…”
Section: Introductionmentioning
confidence: 99%